Current Status and Prospects of Research on Ischemia-Reperfusion Injury and Ferroptosis - Hou, Lin; Li, Xiaodong; Su, Chang; Chen, Kailin; Qu, Maoxing (Frontiers in Oncology, 2022)
The pathogenesis of ischemia-reperfusion injury is not fully understood, and there is no clear early diagnosis standard. At the same time, most of the current clinical treatment methods mainly relieve symptoms, and cannot prevent fundamentally. The mechanism of Ferroptosis has been extensively studied in recent years, but primarily focused on its therapeutic effects on tumors. After careful comparison, it is not difficult to find that the symptoms of ischemia-reperfusion injury often accompanied by increased lipid peroxidation and increased intracellular iron levels are the same as the manifestations of iron-dependent non-apoptotic Ferroptosis. Based on this "coincidence", we launched this survey. After reading a lot of literature, we finally found that Ferroptosis is the first step of ischemia-reperfusion injury, and cell necrosis and inflammation are the subsequent steps secondary to Ferroptosis. In this review, we have collected and sorted out the current knowledge about the role and targets of Ferroptosis in the process of ischemia-reperfusion injury. At the same time, discuss the clinical diagnosis and treatment prospects of Ferroptosis mechanism in ischemia-reperfusion injury on this basis.